2003
DOI: 10.1542/peds.111.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Unlicensed and Off-Label Drug Use in Children Outside the Hospital

Abstract: Efforts to improve pediatric labeling are important and need full support. The present results can be used to focus these efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 17 publications
6
49
1
10
Order By: Relevance
“…First, the study settings have varied; some have focused on admissions [4], some have included only inpatients [5][6][7], others have used a combination of in-patients and new admissions [2], while others have been community-based [8,9]. There is some evidence that off-label prescribing is more prevalent in children who receive a greater number of prescriptions from their GPs, and in those who require a greater number of referrals to specialist care, and indeed in specialist care per se [15,16]. Second, given the differences in study settings, the types of patients surveyed have been different.…”
Section: Tablementioning
confidence: 99%
“…First, the study settings have varied; some have focused on admissions [4], some have included only inpatients [5][6][7], others have used a combination of in-patients and new admissions [2], while others have been community-based [8,9]. There is some evidence that off-label prescribing is more prevalent in children who receive a greater number of prescriptions from their GPs, and in those who require a greater number of referrals to specialist care, and indeed in specialist care per se [15,16]. Second, given the differences in study settings, the types of patients surveyed have been different.…”
Section: Tablementioning
confidence: 99%
“…On the other hand it has been suggested that offlabel use might weaken the interest of pharmaceutical companies to conduct costly trials and apply for marketing authorization if a product has already widely penetrated the market [6]. The extent and problems of off-label and unlicensed use of medicines in children are well documented [7][8][9].The effects of a later paediatric labelling and age-appropriate formulations (dosage forms) on the extent of off-label and on-label use would be of high interest. Unfortunately, longitudinal studies on the dynamics and development of off-label use in children are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Prescriptions by specialists (outpatient), prescriptions for new drugs, prescriptions for drugs with a low use in the paediatric population, and prescriptions for infants were risk factors for using a systemic drug unlicensed or off-label in that study [27]. Since the indications are not available in pharmacy dispensing data, the indication for prescription of a drug was not evaluated.…”
Section: Discussionmentioning
confidence: 99%